Journal Writing Assistance for IPS Teacher - Syarifuddin, Syarifuddin; Putro, Herry Porda Nugroho; Jumriani, Jumriani; Handy, Muhammad Rezky Noor; Ilhami, M. Ridha; Ramadhani, Muhammad Aqiela (Journal of Social Development, 2024)
Professional in the field of education, it is important for teachers to have various skills, including the ability to write scientific papers. Writing scientific papers not only helps teachers achieve career advancement such as promotions and recognition, but also provides opportunities to gain awards and recognition for their work. However, it is unfortunate that many teachers do not have experience writing scientific articles that are published in journals or being speakers at national or regional seminars. To overcome this, the community service program implemented is training and mentoring for social studies teachers at MGMP Barito Kuala Regency. The steps in this activity include coordination, conveying information, mentoring and evaluation. The results of this program show that the majority of social studies teachers in Barito Regency still do not understand and master the techniques for writing scientific papers in accordance with applicable regulations. Apart from that, participants also stated that one of the main difficulties they faced in compiling articles was difficulty in starting research due to a lack of ideas, which in turn was caused by a lack of reading and writing culture.